Relationship between Molecular Weight Distribution and Particle Size of PVC Resin - Dai1, Yong-Qiang; Zhang2, Li; Jin1, Ri-Guang (Asian Journal of Chemistry, 2013)
Through the study of three grades of low polymerization degree poly(vinyl chloride) resins, the molecular weight distribution of low polymerization degree PVC resins was influenced by the particle size. The number of sub micro particles in low polymerization degree poly(vinyl chloride) resin is related to the molecular weight distribution. The higher the number of sub micro particles are, the higher the molecular weight and molecular weight distribution. It is presented a detailed study on the relationship of the molecular weight distribution and inner morphology.